Outcome of pregnancies in a large cohort of women with acromegaly. (18th April 2018) - Jallad, R.S.; Shimon, I.; Fraenkel, M.; Medvedovsky, V.; Akirov, A.; Duarte, F.H.; Bronstein, M.D.
Summary: Objective: To assess the outcome of pregnancies in a large cohort of women with acromegaly. Design and methods: This is a retrospective analysis of 31 pregnancies in 20 patients with acromegaly. Results: Twenty‐seven pregnancies resulted in healthy offspring, and 4 resulted in abortion. Three patients underwent transsphenoidal surgery during pregnancy. IGF‐1 levels remained elevated during pregnancy in 4 pregnancies and normalized in 23 cases. Fifteen cases were followed during pregnancy without any medical or surgical treatment, and 13 of these exhibited normal IGF‐1 levels. Before or during pregnancy, somatostatin receptor ligands usage was not associated with higher risk for adverse outcomes. Arterial hypertension worsening (45%) and impairment of glucose levels (32%) were the most common complications during pregnancies. There were no maternal or neonatal deaths. One woman delivered twins. Two cases of congenital malformations and one with foetal macrosomia were observed. Caesarean delivery was performed in sixteen cases. Conclusion: Our study confirms the impact of gestation on IGF‐1 levels. However, it also indicates that acromegaly still holds an increased risk for worsening of comorbidities, especially in uncontrolled patients.